Mobile application for online exam management system - Choong, Joe Wei (2023)
As the rapid rise in the number of people using smart devices today, mobile applications have been used to solve many kinds of problems. Although there is various online exam software with different functionalities such as online exam management system, scheduling system, grading system, timing system, recording system, attendance system but lack of mobile application that has an integrated functionalities in the market. Hence, I proposed a mobile application named ‘ProExam’ to manage all the functions that I have stated above for the teachers and students used. Furthermore, the online exam management system allows teachers to create the exam questions for the students to conduct it. Besides, it allows the teachers to set a time limit on the online exam for the students. Above all, a database system will be implemented to keep track of the data of the teachers and students. For this project, I plan to use the Mobile Application Development Life Cycle (MADLC) for developing my mobile application. In short, this project will act as a platform to combine all the functionalities in one application and connect between the teachers and students so that the teachers could have full control of their students.